INTEGRASI NILAI MASIPATURE HUTANABE DALAM PENGEMBANGAN KURIKULUM BERBASIS MODEL MURRAY PRINT DAN ROBERTS S. ZAIS - Yenni Novita Harahap; Indah Pratiwi; Resty Wahyuni; Corry Restuina; Amiruddin Hasibuan (Universitas Negeri Medan, 2026)
Curriculum development that is relevant to local social and cultural contexts is a fundamental necessity in modern education. The curriculum functions not only as an academic framework but also as a medium for transmitting values, shaping character, and strengthening students’ cultural identity. This study aims to describe the integration of Masipature Hutanabe values in curriculum development based on the Murray Print Model and the Roberts S. Zais Model, as well as to analyze its implications for curriculum relevance and students’ character development. This research employed a Research and Development (R&D) approach using a qualitative descriptive method. The stages of curriculum development followed the Murray Print Model, which includes needs analysis, formulation of objectives, development and organization of content, design of learning experiences, and curriculum evaluation. The Roberts S. Zais Model was used as a conceptual framework to strengthen the philosophical and sociological foundations, educational objectives, and evaluation system of the curriculum. Data were collected through document analysis, in-depth interviews, and focus group discussions involving educators and local cultural figures. The findings indicate that Masipature Hutanabe values—reflecting togetherness, mutual cooperation, and social responsibility—can be systematically integrated into learning objectives, curriculum content, instructional strategies, and evaluation processes. The integration of local wisdom values enhances the relevance of learning, strengthens character education, and supports the development of a contextual and sustainable curriculum.